Specular affinities: from (self-)reflexivity to intermediality via "mise en abyme" - Chinita, Fátima (2022)
This essay is a theoretical account of the convergence between cinematic self-reflexivity and intermediality, both being considered for these purposes as self-constructed and self-revealing. Lucien Dallenbach's conception of mise en abyme - a combination of the enunciative surplus at the level of enunciation (whereby intradiegetic creators and spectators are revealed at their activities) with a fictional mirroring at the level of the story itself - is deemed a frame-breaking device that also enables the appropriation of other art forms by cinema. Adapting Gilles Deleuze's theory of the crystal-image (1985) to this intermedial context, I argue in favour of an "inter-media image", consisting of a perpetual flux of qualified media in which the mise en abyme generates a true constellation of ever-new inter-art combinations.